Strategies to Improve Livestock Productivity through Probiotic Supplementation: A Literature Review - Inal Inal (Fakultas Teknologi Pertanian Unsultra, 2025)
Improving livestock productivity is a key objective in the development of the animal husbandry sector. One innovative approach that has gained widespread attention is the use of probiotics as dietary supplements. Probiotics are live microorganisms that confer health benefits to the host when administered in adequate amounts. This literature review aims to examine the role and effectiveness of probiotic supplementation in enhancing the productivity of various livestock species, including ruminants, poultry, and swine. Data were collected from relevant national and international journal publications from 2015 to 2024. The findings indicate that probiotic supplementation can improve feed digestibility, stabilize gut microflora, enhance feed conversion efficiency, and strengthen immune response and reproductive performance in livestock. Moreover, the use of probiotics may reduce the reliance on antibiotics, making it a more environmentally friendly and sustainable strategy. However, its effectiveness is highly influenced by factors such as the type of probiotic, dosage, method of administration, and the physiological condition of the animals. Therefore, properly designed probiotic supplementation strategies can serve as a promising solution to sustainably improve livestock productivity. This review highlights the need for further locally based research and field trials to optimize the application of probiotics in the context of the Indonesian livestock system.